Composite material as well as preparation method and application thereof
By modifying the ordered mesoporous alumina on the surface and grafting perfluorooctylsulfonyl fluoride, a composite material was prepared, which solved the problem of insufficient adsorption capacity of existing adsorbents on PFOS and PFOA, and achieved efficient removal of these pollutants in firefighting water.
Patent Information
- Application Number
- CN202311168226.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-11
AI Technical Summary
The existing fluorine-removing adsorbents have poor adsorption capacity to PFOS and PFOA in firefighting water, making it difficult to effectively remove these persistent organic pollutants.
An ordered mesoporous alumina with amino groups on the surface was prepared by amino branching and perfluorooctylsulfonyl fluoride grafting was prepared to improve the adsorption capacity of PFOS and PFOA.
The composite material significantly improves the adsorption efficiency of PFOS and PFOA, and can achieve saturated adsorption in a short time, effectively removing these pollutants in the firefighting water.
Smart Images

Figure CN119588316A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new functional environmental nanomaterials, and in particular to a composite material and a preparation method and application thereof. Background Art
[0002] Perfluorooctane sulfonate (PFOS) and perfluorooctane sulfonic acid (PFOA) are widely used in foam fire extinguishing agents due to their high surface activity, high chemical stability and high thermal stability. However, PFOS and PFOA are difficult to degrade, which poses serious ecological hazards and environmental pollution problems. Experiments have shown that PFOS does not decompose after being boiled in concentrated sulfuric acid for 1 hour, and can still stably exist in various biodegradation experiments under anaerobic and aerobic conditions. Moreover, it is bioaccumulative and can enter the human body through the respiratory tract, drinking water and other pathways, but it is difficult to be excreted, and eventually it is enriched in the human blood and organs such as the liver, kidneys, and brain. The enrichment concentration of PFOS will gradually increase with the increase of trophic level in the food chain. Even if the concentration of PFOS in aquatic animals is only in the trace range (ng / g), it will be amplified through the food chain and accumulated in the human body, endangering human health. At present, PFOS has been detected in water, organisms, the human body and food. Therefore, countries around the world have successively introduced corresponding laws and regulations to restrict its production and use. In 2009, the United Nations Environment Programme (EPA) adopted the Stockholm Convention on Persistent Organic Pollutants, which listed nine types of substances, including perfluorooctane sulfonate (PFOS) and perfluorooctane sulfonyl fluoride (PFOSF), in the list of persistent organic pollutants.
[0003] The "Comprehensive Wastewater Discharge Standard" (GB8978-1996) and the "Pollutant Discharge Standard for Urban Sewage Treatment Plants" (GB18918-2002) both clearly stipulate that the maximum allowable discharge concentration of fluoride-containing enterprise wastewater discharged into the municipal pipe network is 10 mg / L, and the effluent standard of urban sewage treatment plants is 10 mg / L. That is, the current national standard only requires that the fluoride concentration discharged into the water body reach 10 mg / L. It can be seen that raising the standard of fluoride treatment will be a common problem that the sewage treatment industry will soon face. The treatment of fluoride-containing firefighting water and making it meet the corresponding standards has become a hot research field.
[0004] The treatment methods for fluorine-containing wastewater at home and abroad include: chemical precipitation, adsorption, electrochemical method, reverse osmosis, ion exchange and biological treatment technology. Emerging treatment technologies include photodegradation technology, supercritical elemental iron reduction degradation technology, ultrasonic degradation technology, etc., because these technologies have strict requirements on reaction conditions and are difficult to apply in practice. The adsorption method, which uses solid materials with special structures to adsorb perfluorinated compounds in wastewater, is a wastewater treatment method with promotion value. The adsorption method has the advantages of low cost, easy operation, good effect, less or no secondary pollution problems, and a wide range of adsorption materials. It has gradually become the main method for defluorination and a relatively mature defluorination method. Defluorination by adsorption is to pass fluorine-containing wastewater into an adsorption device or mix it with an adsorbent for stirring and impregnation. The principle of defluorination is that fluoride ions exchange with fluorine-loving groups or other ions on the adsorbent, resulting in a decrease in the fluoride concentration in the water. After the adsorbent absorbs fluoride, it can be regenerated by acid washing and other means, and the defluorination effect of the adsorbent after acid washing remains good. Commonly used solid materials include iron-based adsorbents, aluminum-based adsorbents, rare earth adsorbents, biological adsorbents, etc. Different adsorbents have different specific surface areas, resulting in different adsorption capacities. A good adsorbent should have a larger adsorption capacity and a faster adsorption rate, and be able to reach adsorption equilibrium faster.
[0005] The commonly used aluminum-based adsorbent is activated alumina, which has an adsorption capacity of 0.8 to 2.0 mg / g. The cost of activated alumina for defluorination is low, and the operating cost is low. Therefore, defluorination with activated alumina is the most widely used and effective method. The structure of activated alumina determines its good adsorption function. The number of oxygen ions in the second layer of activated alumina is twice that of the first layer, and the oxygen ions are connected to the aluminum ions. Therefore, aluminum ions are exposed on the surface, which makes it possible to react with F - Combine and achieve the purpose of fluorine removal.
[0006] Since foam fire extinguishing agents and firefighting wastewater contain a lot of organic matter, they will interfere with the adsorption of PFOS and PFOA, and the interaction between pure activated carbon or alumina and perfluorinated compounds is too weak, resulting in limited adsorption effect. In addition, traditional Al2O3 has a low saturated adsorption capacity for perfluorinated compounds due to its amorphous pores, small specific surface area and pore volume. Therefore, it is very necessary to develop an adsorbent with high affinity and rapid removal of PFOS and PFOA in firefighting water. Summary of the invention
[0007] The purpose of the present invention is to overcome the problem that the existing defluorination adsorbent has poor adsorption capacity for PFOS and PFOA in fire-fighting water, and to provide a composite material and a preparation method and application thereof.
[0008] In order to achieve the above object, the present invention provides a composite material in a first aspect. The composite material comprises ordered mesoporous alumina whose surface is modified with amino groups, and perfluorooctane sulfonyl fluoride grafted through the amino groups.
[0009] Preferably, the mesopore size of the composite material is in the range of 6-13 nm, the average pore size is 8-9.8 nm, and the pore volume is 0.7-1 cm 3 / g, with a specific surface area of 230-320m 2 / g.
[0010] A second aspect of the present invention provides a method for preparing a composite material, the method comprising the following steps:
[0011] (1) pre-treating the ordered mesoporous alumina with amino groups to obtain the ordered mesoporous alumina with surface modification of amino groups;
[0012] (2) reacting the ordered mesoporous alumina whose surface is modified with amino groups with perfluorooctane sulfonyl fluoride.
[0013] Preferably, in step (1), the method for preparing the ordered mesoporous alumina comprises:
[0014] (a) mixing an aluminum salt and a template agent, and then stirring to obtain a mixed solution;
[0015] (b) adding a pH adjuster to the mixed solution to adjust the pH value of the system to ≥9, followed by stirring to obtain a gel mixture;
[0016] (c) filtering, washing, drying and calcining the gel mixture in sequence to obtain ordered mesoporous alumina.
[0017] Preferably, in step (a), the aluminum salt is selected from one or more of AlCl3·6H2O, Al(NO3)3, NaAlO2 and aluminum sulfate.
[0018] Preferably, the aluminum salt is AlCl3·6H2O.
[0019] Preferably, in step (a), the template agent is selected from one or more of polyethylene glycol, polyvinyl alcohol and polypropylene alcohol.
[0020] Preferably, the template is polyethylene glycol.
[0021] Preferably, in step (a), the weight ratio of the aluminum salt to the template is 1:0.5-2.
[0022] Preferably, the stirring conditions include: a speed of 200-500 rpm and a time of 20-40 min.
[0023] Preferably, in step (b), the pH adjuster is selected from one or more of ammonia water, ammonium carbonate and sodium hydroxide.
[0024] Preferably, the pH adjuster is aqueous ammonia.
[0025] Preferably, in step (b), the pH value of the system is adjusted to 9-9.5.
[0026] Preferably, in step (b), the stirring conditions include: a speed of 500-800 rpm, a temperature of 40-70° C., and a time of 10-18 h.
[0027] Preferably, in step (c), the drying conditions include: temperature of 40-80° C. and time of 10-24 h.
[0028] Preferably, the calcination conditions include: a temperature of 500-600° C. and a time of 4-6 hours.
[0029] Preferably, in step (1), the specific process of subjecting the ordered mesoporous alumina to amino pretreatment comprises:
[0030] S1: Ordered mesoporous alumina and toluene are mixed, then ultrasonicated, and then heated to 100-120°C, and then 3-aminopropyltriethoxysilane is added for reflux reaction;
[0031] S2: Centrifuge the material obtained after the reflux reaction in step S1, and wash and dry the obtained solid.
[0032] Preferably, in step S1, the ultrasonication time is 5-10 min.
[0033] Preferably, in step S1, the solid-liquid ratio of the ordered mesoporous alumina to toluene is 1 g:40-80 mL.
[0034] Preferably, the solid-liquid ratio of the ordered mesoporous alumina to the 3-aminopropyltriethoxysilane is 1 g: 0.4-0.8 mL.
[0035] Preferably, the conditions of the reflux reaction include: temperature of 100-120° C. and time of 16-24 h.
[0036] Preferably, in step (2), the specific process of reacting the ordered mesoporous alumina with amino groups on its surface with perfluorooctanesulfonyl fluoride comprises:
[0037] (I) mixing perfluorooctane sulfonyl fluoride, chloroform and isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0038] (II) under stirring, the ordered mesoporous alumina modified with amino groups on its surface is mixed with isopropyl ether, and then a perfluorooctane sulfonyl fluoride solution is added dropwise to obtain a mixed solution;
[0039] (III) The mixed solution is reacted, then centrifuged, and the obtained solid is dried.
[0040] Preferably, in step (I), the volume ratio of perfluorooctane sulfonyl fluoride, chloroform and isopropyl ether is 0.6:1.8-2.2:0.9-1.1.
[0041] Preferably, in step (II), the stirring temperature is 0-10°C, and the stirring speed is 800-1200 rpm.
[0042] Preferably, the solid-to-liquid ratio of the ordered mesoporous alumina whose surface is modified with amino groups to isopropyl ether is 1 g: 4-6 mL.
[0043] Preferably, the solid-to-liquid ratio of the ordered mesoporous alumina with amino groups modified on the surface to perfluorooctane sulfonyl fluoride is 1 g: 0.4-2 mL.
[0044] Preferably, in step (III), the reaction conditions include: temperature of 50-70°C and time of 0.5-1h.
[0045] The third aspect of the present invention provides an application of the composite material or the composite material prepared by the preparation method in the adsorption of perfluorooctane sulfonate and perfluorooctane sulfonic acid.
[0046] The present invention adopts a template method to prepare ordered mesoporous alumina, and high-temperature calcination to prepare ordered mesoporous alumina materials. Then, considering the problem that the interaction between pure alumina and perfluoro compounds is too weak, the alumina is functionalized, 3-aminopropyltriethoxysilane is grafted onto the surface of the mesoporous alumina, and the surface-enriched amino functional groups are used to adsorb and anchor perfluorooctane sulfonyl fluoride, and finally a hyperbranched, perfluorooctane sulfonyl fluoride group-rich functionalized alumina material is prepared. The fluorine-philic interaction mechanism between perfluoroalkyl chains and the interaction between partially protonated amines and PFOS / PFOA are used to remove PFOS and PFOA from firefighting wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is the N2 adsorption-desorption curve of the composite material obtained in Example 1;
[0048] Figure 2 is the pore size distribution diagram of the composite material obtained in Example 1. DETAILED DESCRIPTION
[0049] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0050] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0051] The present invention provides a composite material on one hand, comprising ordered mesoporous alumina with amino groups modified on the surface, and perfluorooctane sulfonyl fluoride grafted through the amino groups.
[0052] In the preferred embodiment of the present invention, the mesopore size distribution range of the composite material is 6-13 nm, the average pore size is 8-9.8 nm, and the pore volume is 0.7-1 cm 3 / g, with a specific surface area of 230-320m 2 / g.
[0053] In specific embodiments, the average pore size of the composite material can be 8 nm, 8.5 nm, 8.7 nm, 9 nm, 9.2 nm, 9.5 nm, 9.7 nm or 9.8 nm.
[0054] In a specific embodiment, the pore volume of the composite material can be 0.7 cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g or 1cm 3 / g.
[0055] In a specific embodiment, the specific surface area of the composite material can be 230 m 2 / g, 250m 2 / g, 270m 2 / g、300m 2 / g or 320m 2 / g.
[0056] A second aspect of the present invention provides a method for preparing a composite material, the method comprising the following steps:
[0057] (1) pre-treating the ordered mesoporous alumina with amino groups to obtain the ordered mesoporous alumina with surface modification of amino groups;
[0058] (2) reacting the ordered mesoporous alumina whose surface is modified with amino groups with perfluorooctane sulfonyl fluoride.
[0059] In a preferred embodiment of the present invention, in step (1), the method for preparing the ordered mesoporous alumina comprises:
[0060] (a) mixing an aluminum salt and a template agent, and then stirring to obtain a mixed solution;
[0061] (b) adding a pH adjuster to the mixed solution to adjust the pH value of the system to ≥9, followed by stirring to obtain a gel mixture;
[0062] (c) filtering, washing, drying and calcining the gel mixture in sequence to obtain ordered mesoporous alumina.
[0063] In a preferred embodiment of the present invention, in step (a), the aluminum salt is selected from one or more of AlCl3·6H2O, Al(NO3)3, NaAlO2 and aluminum sulfate, and more preferably AlCl3·6H2O.
[0064] In step (a) of the present invention, under preferred circumstances, it is necessary to first mix the aluminum salt with water to obtain an aluminum salt solution and then mix it with the template. At this time, the solid-liquid ratio of the aluminum salt to water is 1g:15-40mL, specifically 1g:15mL, 1g:30mL, 1g:35mL or 1g:40mL.
[0065] In a preferred embodiment of the present invention, in step (a), the template agent is selected from one or more of polyethylene glycol, polyvinyl alcohol and polypropylene alcohol, and more preferably polyethylene glycol.
[0066] In a preferred embodiment of the present invention, in step (a), the weight ratio of the aluminum salt to the template is 1:0.5-2, specifically 1:0.5, 1:0.7, 1:1, 1:1.2, 1:1.5, 1:1.7 or 1:2.
[0067] In a preferred embodiment of the present invention, in step (a), the stirring conditions include: a speed of 200-500 rpm and a time of 20-40 min.
[0068] In a specific embodiment, in step (a), the stirring speed can be 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm or 500rpm, and the stirring time can be 20min, 22min, 25min, 27min, 30min, 32min, 35min, 37min or 40min.
[0069] In a preferred embodiment of the present invention, in step (b), the pH adjuster is selected from one or more of ammonia water, ammonium carbonate and sodium hydroxide, and is more preferably ammonia water.
[0070] In a preferred embodiment of the present invention, in step (b), the pH value of the system is adjusted to 9-9.5, specifically, it can be adjusted to 9, 9.1, 9.2, 9.3, 9.4 or 9.5.
[0071] In a preferred embodiment of the present invention, in step (b), the stirring conditions include: a speed of 500-800 rpm, a temperature of 40-70° C., and a time of 10-18 h.
[0072] In a specific embodiment, in step (b), the stirring speed can be 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm or 800rpm, the stirring temperature can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, and the stirring time can be 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h or 18h.
[0073] In a preferred embodiment of the present invention, in step (c), the drying conditions include: a temperature of 40-80° C. and a drying time of 10-24 h.
[0074] In a specific embodiment of the present invention, in step (c), the drying temperature can be 40°C, 50°C, 60°C, 70°C or 80°C, and the drying time can be 10h, 13h, 15h, 17h, 20h or 24h.
[0075] In a preferred embodiment of the present invention, in step (c), the calcination conditions include: a temperature of 500-600° C. and a time of 4-6 hours.
[0076] In step (c) of the present invention, after the drying operation is completed, the temperature is raised to 500-600° C. at a heating rate of 1-2° C. / min for calcination.
[0077] In a specific embodiment of the present invention, in step (c), the calcination temperature may be 500°C, 520°C, 540°C, 550°C, 560°C, 580°C or 600°C, and the calcination time may be 4h, 4.5h, 5h, 5.5h or 6h.
[0078] In a preferred embodiment of the present invention, in step (1), the specific process of subjecting the ordered mesoporous alumina to amino pretreatment comprises:
[0079] S1: Ordered mesoporous alumina and toluene are mixed, then ultrasonicated, and then heated to 100-120°C, and then 3-aminopropyltriethoxysilane is added for reflux reaction;
[0080] S2: Centrifuge the material obtained after the reflux reaction in step S1, and wash and dry the obtained solid.
[0081] Preferably, in step S1, the ultrasonic time is 5-10 min, specifically 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.
[0082] In a preferred embodiment, in step S1, the solid-liquid ratio of the ordered mesoporous alumina to toluene is 1 g:40-80 mL, specifically 1 g:40 mL, 1 g:50 mL, 1 g:60 mL, 1 g:70 mL or 1 g:80 mL.
[0083] In a preferred embodiment, in step S1, the solid-liquid ratio of the ordered mesoporous alumina to the 3-aminopropyltriethoxysilane is 1g:0.4-0.8mL, specifically 1g:0.4mL, 1g:0.5mL, 1g:0.6mL, 1g:0.7mL or 1g:0.8mL.
[0084] In step S1 of the present invention, the conditions of the reflux reaction include: temperature of 100-120° C. and time of 16-24 h.
[0085] In a specific embodiment, the temperature of the reflux reaction can be 100°C, 105°C, 110°C, 115°C or 120°C, and the temperature time of the reflux reaction can be 16h, 18h, 20h, 22h or 24h.
[0086] In step S2 of the present invention, the centrifugal conditions include: a rotation speed of 5500-6500 rpm and a time of 15-30 min.
[0087] In a specific embodiment, in step S2, the centrifugal speed is 6000 rpm, and the centrifugal time is 20 min.
[0088] In a specific embodiment of the present invention, in step S2, ethanol is used for washing.
[0089] In a preferred embodiment of the present invention, in step (2), the specific process of reacting the ordered mesoporous alumina with amino groups on its surface with perfluorooctanesulfonyl fluoride comprises:
[0090] (I) mixing perfluorooctane sulfonyl fluoride, chloroform and isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0091] (II) under stirring, the ordered mesoporous alumina modified with amino groups on its surface is mixed with isopropyl ether, and then a perfluorooctane sulfonyl fluoride solution is added dropwise to obtain a mixed solution;
[0092] (III) The mixed solution is reacted, then centrifuged, and the obtained solid is dried.
[0093] In a preferred embodiment of the present invention, in step (I), the volume ratio of perfluorooctane sulfonyl fluoride, chloroform and isopropyl ether is 0.6:1.8-2.2:0.9-1.1.
[0094] In a specific embodiment, in step (I), the volume ratio of the perfluorooctane sulfonyl fluoride to the chloroform can be 0.6:1.8, 0.6:1.9, 0.6:2, 0.6:2.1 or 0.6:2.2, and the volume ratio of the perfluorooctane sulfonyl fluoride to the isopropyl ether is 0.6:0.9, 0.6:1 or 0.6:1.1.
[0095] In a preferred embodiment of the present invention, in step (II), the stirring temperature is 0-10°C, and the stirring speed is 800-1200 rpm.
[0096] In a specific embodiment, in step (II), the stirring temperature can be 0°C, 2°C, 5°C, 7°C or 10°C, and the stirring speed can be 800 rpm, 900 rpm, 1000 rpm, 1100 rpm or 1200 rpm.
[0097] In a preferred embodiment of step (II), the solid-liquid ratio of the ordered mesoporous alumina modified with amino groups on its surface to isopropyl ether is 1 g:4-6 mL, specifically 1 g:4 mL, 1 g:5 mL or 1 g:6 mL.
[0098] In a preferred embodiment of the present invention, the solid-to-liquid ratio of the ordered mesoporous alumina modified with amino groups on the surface to perfluorooctane sulfonyl fluoride is 1g:0.4-2mL, specifically 1g:0.4mL, 1g:0.5mL, 1g:0.6mL, 1g:0.7mL, 1g:0.8mL, 1g:0.9mL, 1g:1mL, 1g:1.1mL, 1g:1.2mL, 1g:1.3mL, 1g:1.4mL, 1g:1.5mL, 1g:1.6mL, 1g:1.7mL, 1g:1.8mL, 1g:1.9mL or 1g:2mL.
[0099] In a preferred embodiment of the present invention, in step (II), in order to allow perfluorooctane sulfonyl fluoride to fully react with amino ordered mesoporous alumina, the perfluorooctane sulfonyl fluoride solution needs to be slowly added dropwise, and the dropping speed needs to be controlled.
[0100] Therefore, in a preferred embodiment, in step (II), the dropping speed is 3-10 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution is 90-120 μL.
[0101] In a specific embodiment, in step (II), the dropping speed can be 3 drops / min, 4 drops / min, 5 drops / min, 6 drops / min, 7 drops / min, 8 drops / min, 9 drops / min or 10 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution can be 90 μL, 95 μL, 100 μL, 105 μL, 110 μL, 115 μL or 120 μL.
[0102] In a preferred embodiment of the present invention, in step (III), the reaction conditions include: temperature of 50-70° C. and reaction time of 0.5-1 h.
[0103] In a specific embodiment of step (III), the reaction temperature can be 50°C, 55°C, 60°C, 65°C or 70°C, and the reaction time can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h or 1h.
[0104] In step (III) of the present invention, the centrifugal conditions include: a rotation speed of 5500-6500 rpm and a time of 15-30 min.
[0105] In a specific embodiment, in step (III), the centrifugal speed is 6000 rpm and the centrifugal time is 20 min.
[0106] The third aspect of the present invention provides an application of the composite material or the composite material prepared by the preparation method in the adsorption of perfluorooctane sulfonate and perfluorooctane sulfonic acid.
[0107] This method uses a template method to prepare ordered mesoporous alumina. First, a template agent of a certain structure is selected, and then a reactant raw material with chemical activity is added thereto to generate a precursor through a physical and chemical process. Then, the template agent is removed by washing and roasting, thereby preparing an ordered mesoporous alumina with a certain pore structure and pore size. This method can effectively control the pore structure of the product. Ordered mesoporous alumina has the advantages of good mechanical stability, specific surface area and pore structure, easy control, low price, and rich crystal forms. Then, the ordered mesoporous alumina is functionalized, and amino groups are grafted onto the surface of the ordered mesoporous alumina. Then, the amino functional groups enriched on the surface are used to adsorb and anchor perfluorooctane sulfonyl fluoride to prepare a hyperbranched functionalized alumina material rich in perfluorooctane sulfonyl fluoride groups.
[0108] The invention uses an ordered mesoporous alumina material with a large pore size and a high specific surface area as a matrix, carries out surface amino group treatment and grafts hyperbranched perfluorooctane sulfonyl fluoride thereon (by changing the added amounts of 3-aminopropyltriethoxysilane and perfluorooctane sulfonyl fluoride, the amount of grafted functionalized alumina targeting groups can be regulated), and utilizes the amino group and hyperbranched perfluorooctane functional groups enriched on the surface of the matrix to adsorb and anchor perfluorooctane sulfonate in foam fire extinguishing agents and firefighting wastewater; and flexibly regulates the pH value of the solution to protonate the amino functional groups, thereby providing targeting sites for the adsorption of perfluorooctane sulfonate.
[0109] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.
[0110] Example 1
[0111] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 6.0 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:1.11, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0112] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 60° C., and time of 12 h) to obtain a gel mixture;
[0113] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. at a heating rate of 1° C. / min in a muffle furnace, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina B1;
[0114] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.6 mL of 3-aminopropyltriethoxysilane was added, and the reaction was continued at this temperature (110° C.) for 18 h under reflux;
[0115] (5) The material obtained after the reflux reaction is centrifuged (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), the obtained solid is washed with ethanol, and then dried to obtain ordered mesoporous alumina B2 with surface modified with amino groups;
[0116] (6) mixing 0.6 mL of perfluorooctane sulfonyl fluoride with a mixed solution of 2 mL of chloroform and 1 mL of isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0117] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0118] (8) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain the composite material A1.
[0119] Example 2
[0120] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 6.0 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:1.11, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0121] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 60° C., and time of 12 h) to obtain a gel mixture;
[0122] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0123] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.4 mL of 3-aminopropyltriethoxysilane was added, and the reaction was continued at this temperature (110° C.) for 18 h under reflux;
[0124] (5) centrifuging the material obtained after the reflux reaction (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), washing the obtained solid with ethanol, and then drying to obtain ordered mesoporous alumina with surface modified with amino groups;
[0125] (6) mixing 0.6 mL of perfluorooctane sulfonyl fluoride with a mixed solution of 2 mL of chloroform and 1 mL of isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0126] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0127] (8) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain composite material A2.
[0128] Example 3
[0129] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 6.0 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:1.11, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0130] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 60° C., and time of 12 h) to obtain a gel mixture;
[0131] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0132] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.8 mL of 3-aminopropyltriethoxysilane was added, and the reaction was continued at this temperature (110° C.) under reflux for 18 h;
[0133] (5) centrifuging the material obtained after the reflux reaction (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), washing the obtained solid with ethanol, and then drying to obtain ordered mesoporous alumina with surface modified with amino groups;
[0134] (6) 0.8 mL of perfluorooctane sulfonyl fluoride was mixed with a mixed solution of 2.7 mL of chloroform and 1.4 mL of isopropyl ether (the volume ratio of perfluorooctane sulfonyl fluoride, chloroform and isopropyl ether was 0.6:2.025:1.05) to obtain a perfluorooctane sulfonyl fluoride solution;
[0135] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0136] (8) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain composite material A3.
[0137] Example 4
[0138] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 6.0 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:1.11, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0139] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 60° C., and time of 12 h) to obtain a gel mixture;
[0140] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0141] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.6 mL of 3-aminopropyltriethoxysilane was added, and the reaction was refluxed at this temperature for 18 h;
[0142] (5) centrifuging the material obtained after the reflux reaction (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), washing the obtained solid with ethanol, and then drying to obtain ordered mesoporous alumina with surface modified with amino groups;
[0143] (6) mixing 1.2 mL of perfluorooctane sulfonyl fluoride with a mixed solution of 4 mL of chloroform and 2 mL of isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0144] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0145] (8) The mixture was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain composite material A4.
[0146] Example 5
[0147] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 6.0 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:1.11, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0148] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 60° C., and time of 12 h) to obtain a gel mixture;
[0149] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0150] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.6 mL of 3-aminopropyltriethoxysilane was added, and the reaction was continued at this temperature (110° C.) for 18 h under reflux;
[0151] (5) centrifuging the material obtained after the reflux reaction (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), washing the obtained solid with ethanol, and then drying to obtain ordered mesoporous alumina with surface modified with amino groups;
[0152] (6) 1.0 mL of perfluorooctane sulfonyl fluoride was uniformly mixed with a mixed solution of 3.3 mL of chloroform and 1.7 mL of isopropyl ether (the volume ratio of perfluorooctane sulfonyl fluoride, chloroform and isopropyl ether was 0.6:1.98:1.02) to obtain a perfluorooctane sulfonyl fluoride solution;
[0153] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0154] (8) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain composite material A5.
[0155] Example 6
[0156] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 6.0 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:1.11, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0157] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 50° C., and time of 12 h) to obtain a gel mixture;
[0158] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0159] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.6 mL of 3-aminopropyltriethoxysilane was added, and the reaction was continued at this temperature (110° C.) for 18 h under reflux;
[0160] (5) centrifuging the material obtained after the reflux reaction (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), washing the obtained solid with ethanol, and then drying to obtain ordered mesoporous alumina with surface modified with amino groups;
[0161] (6) mixing 0.6 mL of perfluorooctane sulfonyl fluoride with a mixed solution of 2 mL of chloroform and 1 mL of isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0162] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0163] (8) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain composite material A6.
[0164] Example 7
[0165] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 6.0 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:1.11, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0166] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 70° C., and time of 12 h) to obtain a gel mixture;
[0167] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0168] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.6 mL of 3-aminopropyltriethoxysilane was added, and the reaction was continued at this temperature (110° C.) for 18 h under reflux;
[0169] (5) centrifuging the material obtained after the reflux reaction (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), washing the obtained solid with ethanol, and then drying to obtain ordered mesoporous alumina with surface modified with amino groups;
[0170] (6) mixing 0.6 mL of perfluorooctane sulfonyl fluoride with a mixed solution of 2 mL of chloroform and 1 mL of isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0171] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0172] (8) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain the composite material A7.
[0173] Example 8
[0174] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 9.72 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:1.80, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0175] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 60° C., and time of 12 h) to obtain a gel mixture;
[0176] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0177] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.6 mL of 3-aminopropyltriethoxysilane was added, and the reaction was continued at this temperature (110° C.) for 18 h under reflux;
[0178] (5) centrifuging the material obtained after the reflux reaction (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), washing the obtained solid with ethanol, and then drying to obtain ordered mesoporous alumina with surface modified with amino groups;
[0179] (6) mixing 0.6 mL of perfluorooctane sulfonyl fluoride with a mixed solution of 2 mL of chloroform and 1 mL of isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0180] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0181] (8) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain the composite material A8.
[0182] Example 9
[0183] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 3.24 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:0.6, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0184] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 60° C., and time of 12 h) to obtain a gel mixture;
[0185] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0186] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.6 mL of 3-aminopropyltriethoxysilane was added, and the reaction was continued at this temperature (110° C.) for 18 h under reflux;
[0187] (5) centrifuging the material obtained after the reflux reaction (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), washing the obtained solid with ethanol, and then drying to obtain ordered mesoporous alumina with surface modified with amino groups;
[0188] (6) mixing 0.6 mL of perfluorooctane sulfonyl fluoride with a mixed solution of 2 mL of chloroform and 1 mL of isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0189] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0190] (8) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain the composite material A9.
[0191] Example 10
[0192] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 5.2 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:0.96, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0193] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 40° C., and time of 12 h) to obtain a gel mixture;
[0194] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0195] (4) 1 g of the ordered mesoporous alumina obtained in step (3) was dissolved in 60 mL of toluene, and then ultrasonicated for 10 min, and then the oil bath was heated to 110° C., and then 0.6 mL of 3-aminopropyltriethoxysilane was added, and the reaction was continued at this temperature (110° C.) for 18 h under reflux;
[0196] (5) centrifuging the material obtained after the reflux reaction (the centrifugal speed is 6000 rpm and the centrifugal time is 20 min), washing the obtained solid with ethanol, and then drying to obtain ordered mesoporous alumina with surface modified with amino groups;
[0197] (6) mixing 0.6 mL of perfluorooctane sulfonyl fluoride with a mixed solution of 2 mL of chloroform and 1 mL of isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0198] (7) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina modified with amino groups on its surface was dissolved in 5 mL of isopropyl ether and mixed evenly, and then, under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL), and a mixed solution was obtained after the dropping was completed;
[0199] (8) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain the composite material A10.
[0200] Comparative Example 1
[0201] The method of Example 1 was followed, except that 3-aminopropyltriethoxysilane was not added in this comparative example, that is, no amino pretreatment operation was performed. The specific operation was as follows:
[0202] (1) Weigh 5.4 g of aluminum salt (AlCl3·6H2O) and dissolve it in 97.0 mL of deionized water, place it in a constant temperature water bath at 40°C, and stir and mix it evenly on a magnetic stirrer to obtain an aluminum salt solution, then weigh 6.0 g of a template agent (polyethylene glycol PEG-20000), the weight ratio of aluminum salt to template agent being 1:1.11, slowly add it to the aluminum salt solution and mix it, and then continue to stir (stirring conditions include: speed of 300 rpm, time of 30 min), to obtain a transparent mixed solution;
[0203] (2) slowly adding a pH adjuster (ammonia water) to the transparent mixed solution to adjust the pH value of the system to 9.0, and then continuing to stir (stirring conditions include: stirring speed of 600 rpm, temperature of 60° C., and time of 12 h) to obtain a gel mixture;
[0204] (3) filtering the gel mixture, washing the obtained solid with water, transferring it to an oven and drying it at 80° C. for 18 h, then heating it to 550° C. in a muffle furnace at a heating rate of 1° C. / min, and calcining it at 550° C. for 6 h to obtain ordered mesoporous alumina;
[0205] (4) mixing 0.6 mL of perfluorooctane sulfonyl fluoride with a mixed solution of 2 mL of chloroform and 1 mL of isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution;
[0206] (5) Under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), 1 g of ordered mesoporous alumina was dissolved in 5 mL of isopropyl ether and mixed evenly, and then perfluorooctane sulfonyl fluoride solution was slowly added dropwise thereto (the dropping rate was 5 drops / min, and the volume of each drop of perfluorooctane sulfonyl fluoride solution was 100 μL) under stirring conditions (temperature of 0°C, rotation speed of 1000 rpm), and a mixed solution was obtained after the dropping was completed;
[0207] (6) The mixed solution was stirred at 60° C. and 500 rpm for 0.5 h, and then centrifuged (the centrifugal speed was 6000 rpm and the centrifugal time was 20 min). The obtained solid was dried to obtain the composite material D1.
[0208] Test Example 1
[0209] The specific surface area, pore volume and pore size distribution of A1 were measured using a BET adsorption analyzer. The results are as follows: Figure 1 and Figure 2 shown. Figure 1 This is the N2 adsorption-desorption curve of the composite material A1. The results show that the composite material exhibits an H4-type hysteresis loop in the relative pressure range of P / P0=0.6-1.0, and the isotherm belongs to a type IV adsorption equilibrium curve, indicating that the synthesized material has a mesoporous structure. Figure 2 The BJH pore size distribution diagram of composite material A1 shows that the pore size distribution of the mesopores of composite material A1 is narrow, concentrated in the range of 8 to 11 nm, with an average pore size of 9.6 nm and a pore volume of 0.74 cm 3 / g, specific surface area is 250m 2 / g.
[0210] Test Example 2
[0211] The adsorption performance of A1-A10, B1, B2 and D1 on perfluorooctane sulfonate (potassium) solution was measured by high performance liquid chromatography tandem mass spectrometry (HPLC-MS). The test method was as follows: prepare a perfluorooctane sulfonate (potassium) solution with a concentration of 40 mg / L, add 20 mg of A1-A10, B1, B2 and D1 respectively, stir magnetically, bath at 25°C, and adjust the pH value of the system to acidic. Start timing when A1-A10, B1, B2 and D1 are added, take samples at 1, 2, 3, 4, 5 and 6 hours of the experiment, analyze the residual concentration of perfluorooctane sulfonate (potassium) in the solution by HPLC-MS, and calculate the removal efficiency of perfluorooctane sulfonate. The results are shown in Table 1.
[0212] Table 1
[0213]
[0214]
[0215] It can be seen from the results in Table 1 that after 6 hours of reaction, the PFOS removal rates of Examples 1-10 are 98.1%, 96.4%, 98.4%, 98.3%, 98.2%, 98.5%, 95.1%, 91.5%, 85.5% and 96.5%, respectively, that is, the residual PFOS amounts after the reaction are 0.76 mg / L, 1.44 mg / L, 0.64 mg / L, 0.68 mg / L, 0.72 mg / L, 0.60 mg / L, 1.96 mg / L, 3.40 mg / L, 5.80 mg / L and 1.40 mg / L, respectively. The PFOS removal rates of B1, B2 and D1 were 55.3%, 70.8% and 59.4%, respectively, that is, the residual PFOS amounts after the reaction were 17.88 mg / L, 11.68 mg / L and 16.24 mg / L, respectively, which were much lower than the removal rate of the composite material prepared in the example.
[0216] Test Example 3
[0217] The adsorption performance of A1, A3, A6, B1, B2 and D1 on the mixed aqueous solution of perfluorooctane sulfonate (potassium) and alkyl glycoside was determined by high performance liquid chromatography tandem mass spectrometry (HPLC-MS). The test method is as follows: prepare a mixed solution of perfluorooctane sulfonate (potassium) and alkyl glycoside (the concentration of perfluorooctane sulfonate in the mixed solution is 40 mg / L, and the concentration of alkyl glycoside is 100 mg / L), add 20 mg of A1, A3, A6, B1, B2 and D1 respectively, stir magnetically, bath in 25°C water, and adjust the pH value of the system to acidic. Start timing when A1, A3, A6, B1, B2 and D1 are added, take samples when the experiment is carried out for 6 hours, analyze the residual concentration of perfluorooctane sulfonate in the solution by HPLC-MS, and calculate the removal efficiency of perfluorooctane sulfonate. The results are shown in Table 2.
[0218] Table 2
[0219]
[0220] It can be seen from the results in Table 2 that after 6 hours of reaction, the PFOS removal rates of Example 1, Example 3, Example 6, and Example 7 are 96.2%, 96.8%, and 97.0%, respectively, while the PFOS removal rates of B1, B2, and D1 are 44.1%, 58.9%, and 50.5%, respectively. Compared with the solution without adding alkyl glycoside, after adding alkyl glycoside, the alkyl glycoside has little effect on the PFOS adsorption efficiency of the composite material.
[0221] Test Example 4
[0222] The adsorption performance of A1, A3, A6, B1, B2 and D1 on the mixed aqueous solution of perfluorooctane sulfonate (potassium) and sodium dodecyl sulfate was determined by high performance liquid chromatography tandem mass spectrometry (HPLC-MS). The test method is as follows: prepare a mixed solution of perfluorooctane sulfonate (potassium) and sodium dodecyl sulfate (the concentration of perfluorooctane sulfonate (potassium) in the mixed solution is 40 mg / L, and the concentration of sodium dodecyl sulfate is 100 mg / L), add 20 mg of A1, A3, A6, B1, B2 and D1 respectively, stir magnetically, bath in 25°C water, and adjust the pH value of the system to acidic. Start timing when A1, A3, A6, B1, B2 and D1 are added, sample is taken when the experiment is carried out for 6 hours, analyze the residual concentration of perfluorooctane sulfonate (potassium) in the solution by HPLC-MS, and calculate the removal efficiency of perfluorooctane sulfonate (potassium). The results are shown in Table 3.
[0223] Table 3
[0224]
[0225] From the results in Table 3, it can be seen that after 6 hours of reaction, the PFOS removal rates of Example 1, Example 3, Example 6, and Example 7 are 80.1%, 82.4%, and 83.6%, respectively, while the PFOS removal rates of B1, B2, and D1 are 28.5%, 32.8%, and 35.6%, respectively, which are much lower than the removal rate of the composite material prepared in the embodiment. Compared with the case where sodium dodecyl sulfate is not added to the solution, after adding sodium dodecyl sulfate, the adsorption rate of PFOS by the composite material is slightly reduced, but still has a high adsorption rate.
[0226] Combining the experimental results of Test Example 3 and Test Example 4, it can be seen that the adsorption effect of the composite material of the present application on PFOS is not affected by anionic surfactants and non-ionic surfactants.
[0227] Test Example 5
[0228] The adsorption performance of A1, A3, A6, B1, B2 and D1 on the aqueous film-forming foam mixed solution containing perfluorooctane sulfonate was determined by high performance liquid chromatography tandem mass spectrometry (HPLC-MS). The test method is as follows: the aqueous film-forming foam fire extinguishing agent (purchased from Jiangsu Jiangya Fire Technology Co., Ltd.) and water are mixed in a weight ratio of 6:94 to prepare an aqueous film-forming foam mixed solution; a certain amount of perfluorooctane sulfonate is added to the aqueous film-forming foam mixed solution to obtain a mixed solution, and the concentration of perfluorooctane sulfonate (potassium) in the mixed solution is 40 mg / L; then 20 mg of A1, A3, A6, B1, B2 and D1 are added respectively, magnetic stirring is performed, a water bath is placed at 25°C, and the pH value of the system is adjusted to acidic. The timing was started when A1, A3, A6, B1, B2 and D1 were added. Samples were taken when the experiment was carried out for 6 hours. The residual concentration of perfluorooctane sulfonate (potassium) in the solution was analyzed by HPLC-MS, and the removal efficiency of perfluorooctane sulfonate was calculated. The results are shown in Table 4.
[0229] Table 4
[0230]
[0231] It can be seen from the results in Table 4 that after 6 hours of reaction, the PFOS removal rates of Example 1, Example 3, Example 6, and Example 7 are 96.0%, 96.4%, and 96.5%, respectively, while the PFOS removal rates of B1, B2, and D1 are 41.1%, 55.8%, and 49.5%, respectively. This shows that the composite material can efficiently remove PFOS from fire water and has strong anti-interference ability.
[0232] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composite material, characterized in that: The composite material comprises ordered mesoporous aluminum oxide with amino groups modified on the surface and perfluorooctane sulfonyl fluoride grafted through the amino groups.
2. The composite material according to claim 1, characterized in that The mesopore diameter of the composite material ranges from 6 to 13 nm, the average pore diameter is 8 to 9.8 nm, and the pore volume is 0.7 to 1 cm 3 / g, with a specific surface area of 230-320m 2 / g.
3. A method for preparing a composite material, characterized in that: The preparation method comprises the following steps: (1) pre-treating the ordered mesoporous alumina with amino groups to obtain the ordered mesoporous alumina with surface modification of amino groups; (2) reacting the ordered mesoporous alumina whose surface is modified with amino groups with perfluorooctane sulfonyl fluoride.
4. The preparation method according to claim 3, characterized in that: In step (1), the method for preparing the ordered mesoporous alumina comprises: (a) mixing an aluminum salt and a template agent, and then stirring to obtain a mixed solution; (b) adding a pH adjuster to the mixed solution to adjust the pH value of the system to ≥9, followed by stirring to obtain a gel mixture; (c) filtering, washing, drying and calcining the gel mixture in sequence to obtain ordered mesoporous alumina.
5. The preparation method according to claim 4, characterized in that: In step (a), the aluminum salt is selected from one or more of AlCl3·6H2O, Al(NO3)3, NaAlO2 and aluminum sulfate; Preferably, the aluminum salt is AlCl3·6H2O.
6. The preparation method according to claim 4 or 5, characterized in that: In step (a), the template agent is selected from one or more of polyethylene glycol, polyvinyl alcohol and polypropylene alcohol; Preferably, the template is polyethylene glycol.
7. The preparation method according to claim 4, characterized in that: In step (a), the weight ratio of the aluminum salt to the template is 1:0.5-2; Preferably, the stirring conditions include: a speed of 200-500 rpm and a time of 20-40 min.
8. The preparation method according to claim 4, characterized in that: In step (b), the pH adjuster is selected from one or more of ammonia water, ammonium carbonate and sodium hydroxide; Preferably, the pH adjuster is aqueous ammonia.
9. The preparation method according to claim 4 or 8, characterized in that: In step (b), the pH value of the system is adjusted to 9-9.
5.
10. The preparation method according to claim 4, characterized in that: In step (b), the stirring conditions include: a speed of 500-800 rpm, a temperature of 40-70° C., and a time of 10-18 h.
11. The preparation method according to claim 4, characterized in that: In step (c), the drying conditions include: temperature of 40-80°C and time of 10-24h; Preferably, the calcination conditions include: a temperature of 500-600° C. and a time of 4-6 hours.
12. The preparation method according to claim 3 or 4, characterized in that: In step (1), the specific process of pre-treating the ordered mesoporous alumina by amino treatment includes: S1: Ordered mesoporous alumina and toluene are mixed, then ultrasonicated, and then heated to 100-120°C, and then 3-aminopropyltriethoxysilane is added for reflux reaction; S2: Centrifuge the material obtained after the reflux reaction in step S1, and wash and dry the obtained solid.
13. The preparation method according to claim 12, characterized in that: In step S1, the ultrasonication time is 5-10 minutes.
14. The preparation method according to claim 12 or 13, characterized in that: In step S1, the solid-liquid ratio of the ordered mesoporous alumina to toluene is 1 g: 40-80 mL; Preferably, the solid-liquid ratio of the ordered mesoporous alumina to the 3-aminopropyltriethoxysilane is 1 g: 0.4-0.8 mL; Preferably, the conditions of the reflux reaction include: temperature of 100-120° C. and time of 16-24 h.
15. The preparation method according to claim 3, characterized in that: In step (2), the specific process of reacting the ordered mesoporous alumina with amino groups on its surface with perfluorooctanesulfonyl fluoride includes: (I) mixing perfluorooctane sulfonyl fluoride, chloroform and isopropyl ether to obtain a perfluorooctane sulfonyl fluoride solution; (II) under stirring, the ordered mesoporous alumina modified with amino groups on its surface is mixed with isopropyl ether, and then a perfluorooctane sulfonyl fluoride solution is added dropwise to obtain a mixed solution; (III) The mixed solution is reacted, then centrifuged, and the obtained solid is dried.
16. The preparation method according to claim 15, characterized in that: In step (I), the volume ratio of perfluorooctane sulfonyl fluoride, chloroform and isopropyl ether is 0.6:1.8-2.2:0.9-1.
1.
17. The preparation method according to claim 15, characterized in that: In step (II), the stirring temperature is 0-10°C and the stirring speed is 800-1200 rpm; Preferably, the solid-to-liquid ratio of the ordered mesoporous alumina whose surface is modified with amino groups to isopropyl ether is 1 g: 4-6 mL.
18. The preparation method according to claim 15 or 17, characterized in that: The solid-liquid ratio of the ordered mesoporous alumina with amino groups modified on the surface to perfluorooctane sulfonyl fluoride is 1g:0.4-2mL.
19. The preparation method according to claim 15, characterized in that: In step (III), the reaction conditions include: temperature of 50-70°C and time of 0.5-1h.
20. Use of the composite material according to claim 1 or the composite material prepared by the preparation method according to any one of claims 3 to 19 in the adsorption of perfluorooctane sulfonate and perfluorooctane sulfonic acid.
Citation Information
Patent Citations
Method for preparing ordered mesoporous aluminum oxide in batch
CN101376517A
Perfluoro-capillary extraction monolithic column and preparation method and application thereof
CN102183603A
Application of graphite-phase carbon nitride in removing of perfluorocaprylic acid in water
CN108144572A
Synthesis method and applications of temperature-controlled targeted capture material
CN110465271A
Preparation process of super-hydrophobic waterproof coating film
CN116463040A
Cited By
Amino silane modified ZnAl-LDH adsorbent as well as preparation method and application thereof
CN122352195A